GAMBARAN STATUS GIZI PADA PASIEN PENYAKIT PARU OBSTRUKTIF KRONIK (PPOK) YANG MENJALANI RAWAT JALAN DI RSUD ARIFIN ACHMAD PEKANBARU - Permatasari, Nia; Saad, Azizman; Christianto, Erwin (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTChronic Obstructive Pulmonary Disease (COPD) is one of pulmonary disease that becomes health problem in world, including Indonesia. Nutritional status is the condition of health of a person that is influenced by the intake and utilisation of nutrients. COPD may affect the nutritional status and cause malnutrition, otherwise malnutrition may increase risk of complications, morbidity and mortality rate of COPD’s patient. Nutritional status and malnutrition also affected the quality of life COPD’s patient. This study was using descriptive methods with crossectional approached. The sampling technique used consecutive sampling. The study was held on February-March 2016 with number of sample is 60 patients with COPD in Pulmonary Polyclinic of Arifin Achmad Pekanbaru general hospital. The result of this study is characteristic based age showed 32 (53,3%) persons were >65 years old, 55 (91,7%) persons were male. Characteristic based on occupation showed 33 (55,0%) persons were retired, 48 (80,0%) persons were ex-smoker, 31 (51,7%) persons had COPD for 1-5 years, and 35 (58,3%) persons with good appetite. Nutritonal status based on Body Mass Index (BMI) showed 28 (47,0%) persons had normal category. Nutritional status based on Mid-upper Arm Circumference (MUAC) measurement showed 48 (80,0%) persons had ideal nutrition category. The risk of malnutrition based on Malnutrition Universal Screening Tool (MUST) showed 26 (43,0%) persons were low risk category.Keywords: COPD outpatients, nutritional status, Malnutrition Universal Screening Tool (MUST).